TXNIP regulates pulmonary inflammation induced by Asian sand dust - So-Won Pak; Woong-Il Kim; Se-Jin Lee; Sin-Hyang Park; Young-Kwon Cho; Joong-Sun Kim; Jong-Choon Kim; Sung-Hwan Kim; In-Sik Shin (Redox Biology)
Asian sand dust (ASD), a seasonal dust storm originating from the deserts of China and Mongolia, affects Korea and Japan during the spring, carrying soil particles and a variety of biochemical components. Exposure to ASD has been associated with the onset and exacerbation of respiratory disorders, although the underlying mechanisms remain unclear. This study investigates ASD-induced pulmonary toxicity and its mechanistic pathways, focusing on the role of thioredoxin-interacting protein (TXNIP). Using TXNIP knock-out (KO) mice and adeno-associated virus (AAV)-mediated TXNIP overexpression transgenic mice, we explored how TXNIP modulates ASD-induced pulmonary inflammation. Mice were exposed to ASD via intranasal administration on days 1, 3, and 5 to induce inflammation. ASD exposure led to significant pulmonary inflammation, evidenced by increased inflammatory cell counts and elevated cytokine levels in bronchoalveolar lavage fluid, as well as heightened protein expression of the TXNIP/NOD-like receptor pyrin domain-containing 3 (NLRP3) inflammasome. TXNIP KO mice exhibited attenuated airway inflammation and downregulation of the NLRP3 inflammasome compared to wild-type controls, while AAV-mediated TXNIP overexpression mice showed exacerbated inflammatory responses, including elevated NLRP3 inflammasome expression, compared to AAV-GFP controls. These findings suggest that TXNIP is a key regulator of ASD-induced pulmonary inflammation.